2017
DOI: 10.1183/13993003.00791-2016
|View full text |Cite
|
Sign up to set email alerts
|

Management of COPD exacerbations: a European Respiratory Society/American Thoracic Society guideline

Abstract: This document provides clinical recommendations for treatment of chronic obstructive pulmonary disease (COPD) exacerbations.Comprehensive evidence syntheses, including meta-analyses, were performed to summarise all available evidence relevant to the Task Force's questions. The evidence was appraised using the Grading of Recommendations, Assessment, Development and Evaluation approach and the results were summarised in evidence profiles. The evidence syntheses were discussed and recommendations formulated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
242
1
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(300 citation statements)
references
References 80 publications
(96 reference statements)
4
242
1
23
Order By: Relevance
“…A history of at least one hospital admission in the previous 12 months was strongly associated with mortality in CHF, but not with mortality or hospitalization in COPD. This finding is in conflict with the previously reported result that a history of moderate to severe exacerbations of COPD is a strong risk factor for mortality and future exacerbations in patients with COPD [31][32][33]. By contrast, we confirmed that previous 12-month hospitalizations are predictors of mortality in patients with CHF [34] and extended this finding to patients with a milder disease (NYHA I and II).…”
Section: Discussioncontrasting
confidence: 57%
“…A history of at least one hospital admission in the previous 12 months was strongly associated with mortality in CHF, but not with mortality or hospitalization in COPD. This finding is in conflict with the previously reported result that a history of moderate to severe exacerbations of COPD is a strong risk factor for mortality and future exacerbations in patients with COPD [31][32][33]. By contrast, we confirmed that previous 12-month hospitalizations are predictors of mortality in patients with CHF [34] and extended this finding to patients with a milder disease (NYHA I and II).…”
Section: Discussioncontrasting
confidence: 57%
“…It is especially striking that although a blood gas analysis is recommended in the GOLD guidelines [1] , this examination was performed on only 85.6% of the patients fulfilling the criteria for severe exacerbation and thus requiring hospitalization. NIV reduces the mortality rate and the length of ICU and hospital stay [16] ; yet only 66.7% of the patients fulfilling the ABG criteria for NIV received this therapy, and only 30.0% of those requiring IMV were treated accordingly. In the other European countries, NIV was administered to only 51.3% of the patients fulfilling the ABG criteria, and IMV to only 15.2% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to decision (EtD) framework developed by the GRADE Working Group acknowledges the importance of patients’ values and preferences 10. Following this framework, the 2017 guidelines on prevention of COPD exacerbations published by the European Respiratory Society and the American Thoracic Society added a paragraph on “values and preferences” to every treatment recommendation 11. For example, the statement accompanying the conditional recommendation to use oral mucolytic agents to prevent future COPD exacerbations reads: “This recommendation places a high value on avoiding hospitalisations and a lower value on the cost and burden of taking daily medication.”…”
Section: How Do Guidelines Handle Burden Of Treatment?mentioning
confidence: 99%
“…The 2017 guidelines on prevention of COPD exacerbations make a conditional recommendation for initiation of pulmonary rehabilitation within three weeks after hospital discharge 11. The current “values and preferences” section states: “This recommendation places a high value on improving clinical outcomes and a lower value on the burden and cost of pulmonary rehabilitation.”…”
Section: Integration Of Treatment Burden Into Guidelinesmentioning
confidence: 99%